EFFECT OF HERBICIDES ON MANAGEMENT OF WEEDS IN LAWN - SIDDAPPA,; K. V. JAYAPRASAD,; M. T. SANJAY, (The Bioscan, 2015)
Field experiment was conducted during the period from November to December 2013 to February to March 2014 to manage the sedge and broad leaf weeds in lawn.The major weed species was observed in the experimental plots were Cyperus rotundus (sedge), Panicum repens, Digitaria marginata (among grasses), Ageratum conyzoides, Bidens spilosa, Alternanthera sessilis, Cinebra didyma, Desmodium triflorum, Emilia sanchifolia, Euphorbia hirta, Oxalis latifolia and minor weeds were Borreria articularis, Chromalaena odorata, Cyanotis spp., Mimosa pudica, Parthenium hysterophorus, Phyllanthus niruri, Sida acuta, Tridax procumbens. Among the herbicides at 60 days after application herbicides 2, 4-D dimethyl amine salt 58% EC 10 ml/lit of water,2, 4-D sodium salt 80 WP 4 g/lit water, 2, 4-D dimethyl amine salt 58% EC 7.5 ml/lit of water, 2, 4-D sodium salt 80 WP 2 g/lit water, showed weed control efficiency 92.6, 91.9, 87.7 and 87.4%, respectively as higher than that of hand weeding at 20 days interval (62.8%). Whereas 2, 4-D sodium salt 80 WP 4 g/lit water and 2, 4-D dimethyl amine salt 58% EC 10 ml/lit of water can be suggested for management of sedge and broad leaf weeds in lawn.